Crossroads of war a historical atlas of the Middle East - Barnes, Ian; Ruthven, Malise (The Belknap Press of Harvard University Press, 2014)
From the Bronze Age to the twenty-first century, vying armies have clashed over the territory stretching from the Upper Nile to modern-day Iraq and Iran. Crossroads of War captures five millennia of conflict and conquest in detailed full-color maps, accompanied by incisive, accessible commentary.